Barbie, spy squad [videorecording (DVD)] (Universal Studios Home Entertainment, 2016)
Barbie and her best friends Teresa and Renee transform from hard-working gymnasts to undercover secret agents in this exciting, action-packed adventure! When their amazing gymnastics skills catch the eye of a top-secret spy agency, the girls are soon following clues to a gem-stealing cat burglar who has escaped everyone on the case. With their high-tech gadgets, glam disguises and cute robo-pets, can they prove that smarts and teamwork can get the mission accomplished?